Small and Medium‐Sized Towns in Europe: Conceptual, Methodological and Policy Issues. (27th February 2017) - Servillo, Loris; Atkinson, Rob; Hamdouch, Abdelillah
Abstract: Despite that small and medium‐sized towns (SMSTs) have been, and continue to be, a central part of the history of Europe, these places have largely been neglected by urban research. The ESPON TOWN project, on which this Special Issue builds, sought to redress this neglect performing a comparative analysis of their position and role across Europe. In this introductory paper we discuss some of the theoretical and methodological challenges when it came to identifying, studying and analysing SMSTs and the theoretical framework developed to inform our understanding of SMSTs. In particular, three themes are discussed. The first one is about the ontological problem of defining a town. Administrative, morphological and functional perspectives are considered. The second one reflects on a wide array of interpretative approaches about the relationship between towns and their regional context. The third one is about the thematic and multi‐scalar perspectives that can characterise the policy approach to towns.